Polemik Manusia Perdana Antara Islam dan Barat - Rosyid, Moh. (Analisis: Jurnal Studi Keislaman, 2019)
Al Quran as a source of Muslim inspiration has not been exhumed for the benefit of life. It makes no difference to explore the polemic about early humans when juxtaposed with Western concepts that Charles Darwin revealed in the Theory of Evolution in 1859. The Qur'an does not provide complete data that Adam was the first human being on earth, predicted there were three previous people before Adam, namely Banul Jan, Banul Tires, and Ijajil from the last genie. It's just that the interpretation of the verse of the Qur'an states that Adam was the first man. Thus, this polemic requires deepening which includes cross-scientific knowledge as dialogue capital. The Qur'an emphasizes that the stages of the process of human creation have been fixed, the elements of events include the body (body), life (nafs), spirit (spirit), human events do not go through phases that develop form, as Darwin proposes that humans are allied to chimpanzees. This text uses the method of interpretation of bi ar-Ra'yi or al-'aqli with the type of interpretation of the maudhu'i and the study of the codification era, with the interpretation of muqorin in examining the theme. Dialogizing the contents of the Qur'an with Western theory is not a taboo matter, as Muslim scientists must be in principle that the shrewdness of human reason must submit to the truth of the message in the Qur'an